TRADITIONAL GAMES AS A PEDAGOGICAL STRATEGY IN MIDDLE SCHOOL - Garbossa, Teresina Funez; Renosto, Emanuelli; Funez, Neivair; Bellini, Ilone Cristina; da Silva, José Amauri Siqueira; Nyamien, Francy Rodrigues Guia (Seven Editora, 2025)
Traditional play activities play a fundamental role in the comprehensive development of children, encompassing cognitive, social, emotional, and physical aspects. This study investigated the perceptions of 31 elementary school teachers in public schools in Concórdia, SC, Brazil, regarding the importance of these playful practices in the school context. A mixed-methods approach was employed, combining questionnaires and semi-structured interviews to analyze the frequency of use, observed impacts on students’ behavior and learning, and the challenges faced by teachers. The results indicate that most teachers recognize the benefits of traditional play, emphasizing its relevance for socialization, socio-emotional development, collaborative learning, and cultural preservation. However, factors such as lack of time, limited physical space, and the influence of digital technologies still hinder its regular application. The findings highlight the need for intentional pedagogical planning, continuous teacher training, and strategies that integrate traditional play into the school curriculum, valuing both educational tradition and contemporary demands. DOI: https://doi.org/10.56238/sevened2025.038-075